Pengaruh Stakeholder Pressure dan Corporate Governance Terhadap Kualitas Pengungkapan Sustainability Report Perusahaan Peserta ASRRAT Periode 2022-2025 - Nurfiqa Mutia; Ulta Rastryana; Rini Larasati Irawan (PT. Karya Inovatif Nusantara, 2026)
Environmental problems arising from corporate operational activities have become one of the main challenges in the era of globalization. Companies are required to pay attention to social and environmental impacts through quality sustainability report disclosures. This study aims to analyze the effect of Stakeholder Pressure and Corporate Governance on the Quality of Sustainability Report Disclosure in Companies Participating in the Asia Sustainability Reporting Rating (ASRRAT) for the Period 2022–2025. This study uses a quantitative approach involving a sample of 12 companies selected through purposive sampling technique. Data were collected through documentation of annual reports and sustainability reports, then analyzed using multiple linear regression with SPSS. The results show that Stakeholder Pressure has no significant effect on the Quality of Sustainability Report Disclosure with a t-value of 0.218 (p = 0.829), while Corporate Governance shows a positive and significant effect with a t-value of 2.337 (p = 0.024). Simultaneously, Stakeholder Pressure and Corporate Governance significantly affect the Quality of Sustainability Report Disclosure with an F-value of 3.945 (p = 0.026) and a contribution of 14.9%. This study recommends strengthening effective corporate governance through increasing the proportion of independent commissioners, audit committee effectiveness, and managerial ownership, as well as regular evaluation of sustainability reporting practices to improve disclosure quality and promote organizational accountability on an ongoing basis.